Determinación de la incidencia de dirofilaria immitis en perros domésticos de más de un año, mediante la utilización de dos métodos de diagnóstico de laboratorio en la clínica veterinaria 101 dalmatas, cantón Santo Domingo, provincia Santo Domingo de los Tsáchilas - Tapia Huerta, Washington Daniel (2015)
Dirofilaria immitis is the name of a parasitic nematode of the dog, which is the final host, but this could infect to cats, cattle, foxes, coyotes, ferrets, sea lions and in very few time to humans. The reproductive phase in the lifecycle of the adult parasite reside in the pulmonary arteries mainly and in the right ventricle of the animal’s heart, in which can live for several years, producing the canine dirofilariosis. The D. immitis is transmitted by the mosquito bite and in humans this forms an injury in the lung, which can produce a pulmonary thrombosis and, seldom a cardiac thrombosis. The lung injury could be seeing in the lung radiography as granulomatous lesions in stack of coins shape, in a similar way as a malignant lesion requiring sometimes surgery which reveals a parasitic infection rather than cancer....